# Which of the following is not true always?

- (a) If \[f\left( x \right)\] is not continuous at \[x=a\], then it is not differentiable at \[x=a\].

(b) If \[f\left( x \right)\] is continuous at \[x=a\], then it is differentiable at \[x=a\].

(c) If \[f\left( x \right)\] and \[g\left( x \right)\] are differentiable at \[x=a\], then \[f\left( x \right)+g\left( x \right)\] is also differentiable at \[x=a\].

(d) If a function \[f\left( x \right)\] is continuous at \[x=a\], then \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] exists.

- (a) If \[f\left( x \right)\] is not continuous at \[x=a\], then it is not differentiable at \[x=a\].

Answer

Verified

363k+ views

Hint: Use the definition of continuity and differentiability of the functions and check each of the given options. Also, take any function which satisfies the given conditions and then check if the given statement is true or false.

Complete step-by-step answer:

We have to check if each of the given options is true or false based on the definition of continuity.

We will check the first statement which says that if \[f\left( x \right)\] is not continuous at \[x=a\], then it is not differentiable at \[x=a\].

We know that a function is differentiable at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\] exists and \[f'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\].

We can rewrite \[f\left( x \right)\] as \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\left( x-a \right)+f\left( a \right)\]. As \[f\left( x \right)\] is not continuous, \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] does not exist.

Thus, \[\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\left( x-a \right)+f\left( a \right)\] does not exist as well. As \[\underset{x\to a}{\mathop{\lim }}\,\left( x-a \right)\] and \[\underset{x\to a}{\mathop{\lim }}\,f\left( a \right)\] exists, it means \[\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\] does not exist.

We can also prove this by considering functions \[f\left( x \right)=2\] for \[x\ge 0\] and \[f\left( x \right)=x+1\] for \[x<0\].

As we can see that \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,f\left( x \right)=1\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,f\left( x \right)=2\], \[f\left( x \right)\] is not continuous at \[x=0\].

Also, we observe \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=0\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=1\]. Thus, \[f\left( x \right)\] is not differentiable at \[x=0\].

Hence, the first statement is true.

Now, we will consider the second statement which states that if \[f\left( x \right)\] is continuous at \[x=a\], then it is differentiable at \[x=a\].

This statement is not always true. Consider the function \[f\left( x \right)=\left| x \right|\]. We observe that \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,f\left( x \right)=0=\underset{x\to {{0}^{+}}}{\mathop{\lim }}\,f\left( x \right)=0=f\left( 0 \right)\]. Thus, \[f\left( x \right)\] is continuous at \[x=0\]. However, we have \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=-1\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=1\]. Thus, \[f\left( x \right)\] is not differentiable at \[x=0\].

Hence, the second statement is not always true.

We will now consider third statement which states that if \[f\left( x \right)\] and \[g\left( x \right)\] are differentiable at \[x=a\], then \[f\left( x \right)+g\left( x \right)\] is also differentiable at \[x=a\].

This statement is always true as we have \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=f'\left( a \right),\underset{x\to a}{\mathop{\lim }}\,\dfrac{g\left( x \right)-g\left( a \right)}{x-a}=g'\left( a \right)\], thus, we have \[f'\left( a \right)+g'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)+g\left( x \right)-f\left( a \right)-g\left( a \right)}{x-a}\]. So, \[f\left( x \right)+g\left( x \right)\] is differentiable as well.

Consider the function \[f\left( x \right)=x,g\left( x \right)={{x}^{2}}\]. We have \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=f'\left( a \right)=1,\underset{x\to a}{\mathop{\lim }}\,\dfrac{g\left( x \right)-g\left( a \right)}{x-a}=g'\left( a \right)=2a\]. Also, we observe that \[f'\left( a \right)+g'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)+g\left( x \right)-f\left( a \right)-g\left( a \right)}{x-a}=1+2a\]. Thus, \[f\left( x \right)+g\left( x \right)\] is differentiable as well.

Hence, the third statement is always true.

We will now consider fourth statement which says that if a function \[f\left( x \right)\] is continuous at \[x=a\], then \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] exists.

This is the definition of continuity of a function which states that \[f\left( x \right)\] is continuous at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)\].

We can also prove this by considering the function \[f\left( x \right)=x\]. As \[f\left( x \right)=x\] is continuous at \[x=a\], we have \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)=a\]. Thus, \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] exists as well.

Hence, the fourth statement is always true.

Thus, the only statement which is not always true is the second statement, which is option (b).

Note: To solve this question, one must keep the definition of continuity and differentiability of any function in mind. A function \[f\left( x \right)\] is continuous at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)\] holds. A function \[f\left( x \right)\] is differentiable at \[x=a\] if \[f'\left( a \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\] holds.

Complete step-by-step answer:

We have to check if each of the given options is true or false based on the definition of continuity.

We will check the first statement which says that if \[f\left( x \right)\] is not continuous at \[x=a\], then it is not differentiable at \[x=a\].

We know that a function is differentiable at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\] exists and \[f'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\].

We can rewrite \[f\left( x \right)\] as \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\left( x-a \right)+f\left( a \right)\]. As \[f\left( x \right)\] is not continuous, \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] does not exist.

Thus, \[\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\left( x-a \right)+f\left( a \right)\] does not exist as well. As \[\underset{x\to a}{\mathop{\lim }}\,\left( x-a \right)\] and \[\underset{x\to a}{\mathop{\lim }}\,f\left( a \right)\] exists, it means \[\underset{x\to a}{\mathop{\lim }}\,f'\left( a \right)\] does not exist.

We can also prove this by considering functions \[f\left( x \right)=2\] for \[x\ge 0\] and \[f\left( x \right)=x+1\] for \[x<0\].

As we can see that \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,f\left( x \right)=1\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,f\left( x \right)=2\], \[f\left( x \right)\] is not continuous at \[x=0\].

Also, we observe \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=0\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=1\]. Thus, \[f\left( x \right)\] is not differentiable at \[x=0\].

Hence, the first statement is true.

Now, we will consider the second statement which states that if \[f\left( x \right)\] is continuous at \[x=a\], then it is differentiable at \[x=a\].

This statement is not always true. Consider the function \[f\left( x \right)=\left| x \right|\]. We observe that \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,f\left( x \right)=0=\underset{x\to {{0}^{+}}}{\mathop{\lim }}\,f\left( x \right)=0=f\left( 0 \right)\]. Thus, \[f\left( x \right)\] is continuous at \[x=0\]. However, we have \[\underset{x\to {{0}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=-1\ne \underset{x\to {{0}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( 0 \right)}{x}=1\]. Thus, \[f\left( x \right)\] is not differentiable at \[x=0\].

Hence, the second statement is not always true.

We will now consider third statement which states that if \[f\left( x \right)\] and \[g\left( x \right)\] are differentiable at \[x=a\], then \[f\left( x \right)+g\left( x \right)\] is also differentiable at \[x=a\].

This statement is always true as we have \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=f'\left( a \right),\underset{x\to a}{\mathop{\lim }}\,\dfrac{g\left( x \right)-g\left( a \right)}{x-a}=g'\left( a \right)\], thus, we have \[f'\left( a \right)+g'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)+g\left( x \right)-f\left( a \right)-g\left( a \right)}{x-a}\]. So, \[f\left( x \right)+g\left( x \right)\] is differentiable as well.

Consider the function \[f\left( x \right)=x,g\left( x \right)={{x}^{2}}\]. We have \[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=f'\left( a \right)=1,\underset{x\to a}{\mathop{\lim }}\,\dfrac{g\left( x \right)-g\left( a \right)}{x-a}=g'\left( a \right)=2a\]. Also, we observe that \[f'\left( a \right)+g'\left( a \right)=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)+g\left( x \right)-f\left( a \right)-g\left( a \right)}{x-a}=1+2a\]. Thus, \[f\left( x \right)+g\left( x \right)\] is differentiable as well.

Hence, the third statement is always true.

We will now consider fourth statement which says that if a function \[f\left( x \right)\] is continuous at \[x=a\], then \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] exists.

This is the definition of continuity of a function which states that \[f\left( x \right)\] is continuous at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)\].

We can also prove this by considering the function \[f\left( x \right)=x\]. As \[f\left( x \right)=x\] is continuous at \[x=a\], we have \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)=a\]. Thus, \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)\] exists as well.

Hence, the fourth statement is always true.

Thus, the only statement which is not always true is the second statement, which is option (b).

Note: To solve this question, one must keep the definition of continuity and differentiability of any function in mind. A function \[f\left( x \right)\] is continuous at \[x=a\] if \[\underset{x\to a}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,f\left( x \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,f\left( x \right)=f\left( a \right)\] holds. A function \[f\left( x \right)\] is differentiable at \[x=a\] if \[f'\left( a \right)=\underset{x\to {{a}^{+}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=\underset{x\to {{a}^{-}}}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{f\left( x \right)-f\left( a \right)}{x-a}\] holds.

Last updated date: 29th Sep 2023

â€¢

Total views: 363k

â€¢

Views today: 10.63k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

The poet says Beauty is heard in Can you hear beauty class 6 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the past tense of read class 10 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE